An Efficient Route to N-Monosubstituted Guanidino-Lactams - Tommasi, Sara; Zanato, Chiara; Carabeo, Rey; Mangoni, Arduino A.; Dall’Angelo, Sergio; Zanda, Matteo (Synthesis, 2015)
A small library of guanidino-lactams were synthesized in four steps and good overall yields by following the routes: preparation of guanylating agents, synthesis of protected guanidino-acids, cyclization to fully protected guanidino-lactams, and deprotection to the target compounds. The guanidino-lactams were assayed as antimicrobials on E. coli showing no significant antibiotic activity.
Keywords: guanidines; guanylation; lactams; cyclization; antimicrobials